Analisis Pendapatan dan Produksi Usahatani Padi pada Lahan Irigasi DAS Hilir Bengawan Solo di Kabupaten Bojonegoro - Deviana Diah Probowati; Masahid Masahid (Jurnal Riset Rumpun Ilmu Tanaman, 2025)
Rice is the main source of income for rural communities in Bojonegoro Regency and is one of the main food commodities that is a priority in agricultural economic development both at the national and regional levels, especially Bojonegoro Regency. The Bojonegoro Regency area is crossed by the Bengawan Solo River which is one of the sources of air for rice plants. The purpose of this study was to determine the production and income of rice farming in the Bengawan Solo Hilir Watershed, Bojonegoro Regency. The sample used was 30 farmers taken purposively who had land around the Bengawan Solo Hilir Watershed. The analysis method used was the Cobb Douglas production function method and farm income analysis. The results showed that rice farming in Bojonegoro Regency was profitable. This can be seen from the farm income of Rp. 760,586,000.00. Rice farm income is the difference between revenue and total costs used, which are Rp. 969,050,000 and Rp. 208,464,000, respectively. The production factors used in the model are land, labor, and fertilizer production factors. The production factor that has a significant influence is the land production factor which has a calculated t value of 6.305 which is greater than the t table value of 2.405 at a 95% confidence level.